Between Individuals and Groups: Normative Ambiguity In Indonesia’s Forestry Partnership Regulation - Astrid Amidiaputri Hasyyati; Heppy Hyma Puspytasari; Meita Debi Riyanti (Jurist-Diction, 2026)
Social Forestry is a strategic program of the Indonesian Government aimed at promoting equitable forest management, as regulated under Government Regulation Number 23 of 2021 on Forestry Administration. One of its implementation schemes is Forestry Partnership, further governed by Minister of Environment and Forestry Regulation Number 9 of 2021. Despite its objective of providing legal access for communities to utilize forest areas, the regulation contains normative ambiguity. Article 45 paragraph (3) of the Regulation designates individuals as the subjects of Forestry Partnership approval while simultaneously requiring the formation of groups. This provision is problematic, as the definition of “individuals” under Article 1 point 34 is conceptually distinct from “groups” as defined in Article 1 point 41. This inconsistency has the potential to generate legal uncertainty and administrative obstacles in practical implementation. This study employs normative legal research methods using statutory and conceptual approaches, with normative analysis conducted through extensive interpretation. The findings indicate the need for clearer normative formulation to ensure legal certainty and enhance the effectiveness of Forestry Partnership implementation.